Is Public Spending Determined by Voter Choice of Fiscal Capacity? - Dudley, Leonard; Montmarquette, Claude (The Review of Economics and Statistics, 1992)
Previous models of public spending fail to explain why high inflation rates are distributed non-randomly across countries. In the switching-regime specification proposed here, governments tend to resort to inflationary debt monetarization when the spending level chosen by voters exceeds actual revenue capacity. The voter-choice and fiscal-capacity models of earlier studies are special cases of this framework. Using cross country data for 1970, 1975 and 1980, the authors find that the voter-choice specification applies to most industrialized countries, whereas fiscal capacity appears to constrain government spending in most developing countries. High inflation appears to result from shocks that alter a country's fiscal capacity relative to voters' expectations. Copyright 1992 by MIT Press.